Intake of Beer, Wine and Spirits and Risk of Heavy Drinking and Alcoholic Cirrhosis - MORTEN GRØNBÆK; MAJKEN K JENSEN; DITTE JOHANSEN; THORKILD I A SØRENSEN; ULRIK BECKER (Biological Research, 2004)
Studies have suggested that wine drinkers are at lower risk of death than beer or spirit drinkers. The aim of this study is to examine whether the risk of becoming a heavy drinker or developing alcoholic cirrhosis differs among individuals who prefer different types of alcoholic beverages. In a longitudinal setting we found that both the risk of becoming a heavy or excessive drinker (above 14 and 21 drinks per week for women and above 21 and 35 drinks per week for men) and the risk of developing alcoholic cirrhosis depended on the individuals preference of wine, beer or spirits. We conclude that moderate wine drinkers appear to be at lower risk of becoming heavy and excessive drinkers and that this may add to the explanation of the reported beverage-specific differences in morbidity and mortality.